Intracoronary artery retrograde thrombolysis for ST-segment elevation myocardial infarction with a tortuous coronary artery: A case report and review of the literature - Shen, Mingzhi; Lu, Haihui; Liao, Yichao; Wang, Jian; Guo, Yi; Zhou, Xinger; Nong, Yingqiao; Fu, Zhenhong; Wang, Jihang; Guo, Yuting; Zhao, Shihao; Fan, Li; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Large thrombus burdens of culprit’s blood vessel remain the primary problem in acute myocardial infarction. Case presentation: A 32-year-old Chinese man presented with ST-segment elevation myocardial infarction (STEMI). Coronary angiography revealed that the distal end of the left circumflex was completely blocked by a large amount of thrombus. Microcatheter-directed intracoronary artery retrograde thrombolysis with urokinase led to recovery of coronary blood flow. Because there was no obvious plaque rupture or artery stenosis in the coronary artery, it was only dilated and no stent was implanted. Conclusion: Microcatheter-directed intracoronary artery retrograde thrombolysis can be performed effectively and safely in some STEMI patients with tortuous coronary vessels and large thrombus. (REST or named ICART ClinicalTrials.gov number, ChiCTR1900023849)